Peran Kreativitas Pengrajin Gerabah terhadap Peningkatan Pendapatan Keluarga dalam Perspektif Ekonomi Islam: Studi Kasus Desa Selorejo, Lampung Timur - Rodiyatul Laili (Journal Tafkirul Iqtishodiyyah, 2025)
This study aims to analyze the influence of artisans' creativity in pottery-making in Selo Rejo Village on family income from an Islamic economic perspective. The research employed a qualitative descriptive method with data collected through in-depth interviews with four artisans and two supporting workers. The results show that design innovations, product variations, and marketing strategies via social media and mobile traders significantly increase artisans’ income, for instance, from IDR 1.5 million to IDR 4–5 million per month. This creativity not only enhances the artisans’ family welfare but also creates employment opportunities for the surrounding community. The pottery business complies with Islamic economic principles, including responsible use of resources, earning lawful income, and benefiting the wider community. The study confirms that creativity is a key factor in promoting local economic development and family welfare. Recommendations include further product innovation and village government support through continuous training and guidance to strengthen Selo Rejo’s pottery industry.